Difficult tracheal intubation in neonates and infants. NEonate and Children audiT of Anaesthesia pRactice IN Europe (NECTARINE): a prospective European multicentre observational study. (June 2021) - Disma, Nicola; Virag, Katalin; Riva, Thomas; Kaufmann, Jost; Engelhardt, Thomas; Habre, Walid; ,; ,; Breschan, Christian; Likar, Rudolf; Platzer, Manuela; Edelman, Isole; et al.
Abstract: Background: Neonates and infants are susceptible to hypoxaemia in the perioperative period. The aim of this study was to analyse interventions related to anaesthesia tracheal intubations in this European cohort and identify their clinical consequences. Methods: We performed a secondary analysis of tracheal intubations of the European multicentre observational trial (NEonate and Children audiT of Anaesthesia pRactice IN Europe [NECTARINE]) in neonates and small infants with difficult tracheal intubation. The primary endpoint was the incidence of difficult intubation and the related complications. The secondary endpoints were the risk factors for severe hypoxaemia attributed to difficult airway management, and 30 and 90 day outcomes. Results: Tracheal intubation was planned in 4683 procedures. Difficult tracheal intubation, defined as two failed attempts of direct laryngoscopy, occurred in 266 children (271 procedures) with an incidence (95% confidence interval [CI]) of 5.8% (95% CI, 5.1–6.5). Bradycardia occurred in 8% of the cases with difficult intubation, whereas a significant decrease in oxygen saturation (SpO2 <90% for 60 s) was reported in 40%. No associated risk factors could be identified among co-morbidities, surgical, or anaesthesia management. Using propensity scoring to adjust for confounders, difficult anaesthesia tracheal intubation did not lead to an increase in 30 and 90 day morbidity or mortality. Conclusions: The results of the present study demonstrate a high incidence of difficult tracheal intubation in children less than 60 weeks post-conceptual age commonly resulting in severe hypoxaemia. Reassuringly, the morbidity and mortality at 30 and 90 days was not increased by the occurrence of a difficult intubation event. Clinical trial registration: NCT02350348.